2017
DOI: 10.1364/oe.25.022750
|View full text |Cite
|
Sign up to set email alerts
|

Spatially localized wavelength-selective absorption in morphology-modulated semiconductor nanowires

Abstract: In this study, we proposed morphology-modulated Si nanowires (NWs) with a hexagonal cross-section and numerically investigated their resonant optical absorption and scattering properties. The calculated absorption and scattering efficiency spectra of the NWs exhibited optical resonances that could be controlled by tuning the aspect ratio (AR) of the NW cross-sectional shapes. The spectra also revealed interesting spectral behaviors including resonant peak shifts in the absorption spectrum and asymmetric line s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It has been shown that the light absorption could be increased by engineering the size, geometry, and orientation of the NWs [12][13][14][15][16][17][18]. We have also shown that the light absorption could be further enhanced by introducing a single shell [19,20] or graded dual shells [21].…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that the light absorption could be increased by engineering the size, geometry, and orientation of the NWs [12][13][14][15][16][17][18]. We have also shown that the light absorption could be further enhanced by introducing a single shell [19,20] or graded dual shells [21].…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, various strategies have been implemented to improve the light absorption in the whole solar spectrum range. It was shown that the light absorption could be readily tuned by controlling the size, geometry, and orientation of the NWs [18][19][20][21][22][23][24][25][26]. Moreover, our previous studies [27,28] showed that the light absorption could be further improved by introducing a non-absorbing dielectric shell as the antireflection coating, which was experimentally and numerically demonstrated in the recent studies [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, a great variety of strategies have been employed to improve light-harvesting ability. It has been shown that the light absorption could be readily engineered by controlling the size, geometry and orientation of the NWs [18][19][20][21][22][23][24]. Our previous studies [25][26][27] showed that the light absorption could be further improved by introducing a non-absorbing dielectric shell (or graded dual shells) as the antireflection coating, which was experimentally and numerically demonstrated in the recent studies [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 91%